Osteoradionecrosis and cholesteatoma of external auditory canal in postradiotherapy nasopharyngeal carcinoma patien - Devira Zahara; Agus Multazar (Oto Rhino Laryngologica Indonesiana, 2013)
Background: Osteoradionecrosis and cholesteatoma of the external auditory canal following external-beam radiotherapy as the treatment of nasopharyngeal carcinoma is a rarely found complication. Patients with external auditory canal cholesteatoma (EACC) typically present with chronic otorrhea and dull pain due to the local invasion of squamous tissue into the bony external audioty canal (EAC). Purpose: To remind ENT specialists and general practitioners about the risk osteoradionecrosis and cholesteatoma of external auditory canal in nasopharyngeal carcinoma patient after radioteraphy treatment. Case: We report a case of osteoradionecrosis andcholesteatoma of EAC in nasopharyngeal carcinoma (NPC) patient with complaint of a foul-smelling discharge from her right and left ears. Two years previously she had undergone external-beam radiotherapy to the neck as the treatment for nasopharyngeal carcinoma. Management: The cholesteatoma was removed microscopicaly on local anasthesia. After the cholesteatoma had been removed the right ear result of pure tone audiometry showed mild degree conductive hearing loss (27,7 dB), while the left ear within normal hearing threshold. Conclusion: Osteoradionecrosis and cholesteatoma of external auditory canal could develop as a complication ofradioteraphy in nasopharyngeal carcinoma patient. Keywords: osteoradionecrosis, cholesteatoma, radiotherapy, chronic otorrhea.ABSTRAKLatar belakang: Komplikasi osteoradionekrosis dan kolesteatoma pada liang telinga luar akibat radioterapi pada pengobatan karsinoma nasofaring sangat jarang terjadi. Pasien dengan kolesteatoma liang telinga luar biasanya datang dengan keluhan otore kronis dan nyeri akibat invasi dari jaringan skuamus ke tulang liang telinga luar. Tujuan: Memberi wawasan bagi dokter umum dan spesialis THT-KL tentang adanya risiko osteoradionekrosis dan kolesteatoma pada liang telinga luar akibat radioterapi pada penderita karsinoma nasofaring. Kasus: Dilaporkan satu kasus osteoradionekrosis dan kolesteatoma di liang telinga luar pada penderita karsinoma nasofaring dengan keluhan sekret telinga berbau busuk pada liang telinga kanan dan kiri.Dua tahun sebelumnya pasien tersebut mendapat radioterapi untuk pengobatan karsinoma nasofaring. Penatalaksanaan: Kolesteatoma diangkat secara mikroskopis dengan anestesi lokal. Pemeriksaan audiometri nada murni pascatindakan didapati tuli konduktif derajat ringan (27,7dB) pada telinga kanan sedangkan telinga kiri dalam batas normal. Kesimpulan: Radionekrosis dan kolestatoma liang telinga luar merupakan komplikasi terapi radiasi pada kasus karsinoma nasofaring.Kata kunci: osteoradionekrosis, kolesteatom, radioterapi, otore kronis.